2015
DOI: 10.1097/dcr.0000000000000352
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up After Surgery for Simple and Complex Cryptoglandular Fistulas

Abstract: Surgical fistulotomy is the strongest risk factor for fecal incontinence. The severity of incontinence increases with the complexity of the fistula, negatively influencing quality of life. Special attention should be paid to these patients so as to mitigate symptoms later in life. A shift to sphincter-sparing procedures appears warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 17 publications
0
65
0
3
Order By: Relevance
“…For these patients, options include mucosal advancement flaps, ligation of the internal fistula tract, anal fistula plugs and an increasing number of novel techniques 2 4 9 10…”
Section: Discussionmentioning
confidence: 99%
“…For these patients, options include mucosal advancement flaps, ligation of the internal fistula tract, anal fistula plugs and an increasing number of novel techniques 2 4 9 10…”
Section: Discussionmentioning
confidence: 99%
“…This could also be related to overall comorbidity, however, rather than to the presence of fistula‐in‐ano. In addition, limited but appropriate treatment of complex fistulae is a major concern, since the severity of continence disturbance rises with the complexity of the fistula and diminishes quality of life . Garcia‐Aguilar et al .…”
Section: Discussionmentioning
confidence: 99%
“…This could also be related to overall comorbidity, however, rather than to the presence of fistula-in-ano. In addition, limited but appropriate treatment of complex fistulae is a major concern, since the severity of continence disturbance rises with the complexity of the fistula and diminishes quality of life [21]. Garcia-Aguilar et al [22] questioned 375 patients after surgery for fistula-in-ano and concluded that satisfaction was related to recurrence of the fistula, the development of a continence disturbance and its effects on lifestyle.…”
Section: O196mentioning
confidence: 99%
“…На сьогодні залишається високою частота незадовільних результатів оперативного лікування. Так, кількість рецидивів хронічного парапроктиту спостерігається майже у 40,2 % випадків [5,8]. Це насамперед пов'язано з неліквідованим внутрішнім отвором параректальної нориці, залишенням її стінок і розгалужень в параректальній клітковині як результату недоско-налості і відносно низької інформативності доопераційної діагностики складних форм хронічного парапроктиту [6,7].…”
Section: âñòóïunclassified